Formability of quenching-partitioning-tempering martensitic steel. Issue 1 (3rd April 2019) - Hao, Qingguo; Qin, Shengwei; Liu, Yu; Zuo, Xunwei; Chen, Nailu; Rong, Yonghua
ABSTRACT: A Fe-0.20C-1.49Mn-1.52Si-0.58Cr-0.05Nb (wt%) steel was treated by a novel quenching-partitioning-tempering (Q-P-T) process and traditional quenching and tempering (Q&T) for comparison, respectively. The researches of the mechanical properties and forming limit diagrams reveal that Q-P-T martensitic steel has more retained austenite (10.8%) than the Q&T martensitic steel (less than 3%), which makes Q-P-T martensitc steel possess higher strain hardening exponent and true uniform elongation than the Q&T martensitic steel. The high value of hardening exponent ( n ) and true uniform elongation ( εu ) stem from the low initial dislocation density in martensitic matrix in Q-P-T martensitic steel before deformation and the high strain hardening rate and dislocation absorption by retained austenite (DARA) effect of retained austenite during deformation. Moreover, the n, or the εu, is a most important parameter in all the apparent parameters affecting the formability of metal sheets, and this conclusion is of practical importance in the comparison of several steels' formability.